The Force Exerted by a Muscle Cross-Bridge Depends Directly on the Strength of the Actomyosin Bond - Karatzaferi, Christina (Biophysical Society, 2004)
Myosin produces force in a cyclic interaction, which involves alternate tight binding to actin and to ATP. We have investigated the energetics associated with force production by measuring the force generated by skinned muscle fibers as the strength of the actomyosin bond is changed. We varied the strength of the actomyosin bond by addition of a polymer that promotes protein-protein association or by changing temperature or ionic strength. We estimated the free energy available to generate force by measuring isometric tension, as the free energy of the states that precede the working stroke are lowered with increasing phosphate. We found that the free energy available to generate force and the force per attached cross-bridge at low [Pi] were both proportional to the free energy available from the formation of the actomyosin bond. We conclude that the formation of the actomyosin bond is involved in providing the free energy driving the production of isometric tension and mechanical work. Because the binding of myosin to actin is an endothermic, entropically driven reaction, work must be performed by a “thermal ratchet” in which a thermal fluctuation in Brownian motion is captured by formation of the actomyosin bond.